BIAYA TENAGA KERJA BORONGAN PADA USAHATANI TANAMAN PANGAN MENURUT KELEMBAGAAN LAHAN DAN TENAGA KERJA DI KABUPATEN GUNUNG KIDUL - SUWARTO, SUWARTO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2010)
This research aims to investigate the cost expenditure of contract labor for food crops farm as effect of land and labor institutions in Gunung Kidul Regency. Cost expenditure for contract labor of owner-operator farmer is higher than cost for HB tenant farmer. Most of HB tenant is in region far from city with bad transportation facility. In addition, volume of farm worker owner farmer may be greater due to area of owner-worker farmer have wider relative to area held by HB tenant farmer. In this case, there is no difference in cost expenditure for contract labor among the owner-operator farmers, LKP land tenant, and forestry land borrower.